TINGKAT EFISIENSI INDUSTRI ASURANSI JIWA SYARIAH MENGGUNAKAN PENDEKATAN TWO STAGE DATA ENVELOPMENT ANALYSIS - Benarda Benarda; Ujang Sumarwan; Muhamad Nadratuzzaman Hosen (School of Business, Bogor Agricultural University (SB-IPB), 2016)
This study aims to measure the efficiency of Sharia life insurance in Indonesia during the period of 2011-2014, analyze the influencing factors of the Tabarru’ funding ratio solvency level and funding ratio solvency level of Sharia life insurance companies in Indonesia on the efficiency in formulating policy implications for Sharia life insurance in order to be more efficient. This study used an analytical tool of DEA (Data Envelopment Analysis). The samples were taken purposively, i.e. 14 sharia life insurance companies in Indonesia from 2011-2014, followed by an analysis of Tobit on the second level. The results of the study indicate that the average results of DEA analysis for the entire DMU (Decision Making Unit) has not been efficient, either economic efficiency (overall technical) or CRS with the score of 0,693116, technical efficiency (pure technical) or VRS with the score of 0,776011, and the efficiency score in the scale efficiency of 0.884275, out of the efficiency average score. Meanwhile, the second level analysis (Tobit Analysis) showed that the level of tabarru’ funding ratio solvency has a positive and significant impact on technical and scale efficiency. The level of solvency ratios of company funding have positive and significant impact on economic and scale efficiency.Keywords: Sharia life insurance, DEA, efficiency, tobit